A Revisit of Managerial Finance Theories from an Islamic Finance Perspective - Mamunur Rashid; Muhammad Ali; Islam Abdeljawad (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 22 Issue 2 Page (114–130)